Disturbance rejection for a quadrotor using robust active force control with genetic algorithm. (1st August 2021) - Abdelmaksoud, Sherif I.; Mailah, Musa; Abdallah, Ayman M.
Among the various types of rotorcraft unmanned aerial vehicles (UAVs), the quadrotor is currently one of the most versatile flying machines. However, it is an under-actuated, highly non-linear coupling system. It is also sensitive to external disturbances and uncertainties while tracking certain paths, which can affect its performance and may cause undesirable movements that sometimes lead to the failure of the entire system. This work introduces an innovative hybrid control scheme for a quadrotor model to reject different forms of external disturbances while ensuring stability during trajectory tracking. The proposed control structure incorporates an active force control (AFC) strategy with a proportional-integral-derivative (PID) controller, tuned using the genetic algorithm (GA) method, known as the (PIDAFC-GA) scheme. In addition, a sensitivity analysis of the effect of utilising the partial-to-total output of the AFC signal was investigated. The hybrid PID-AFC-GA controller gives superior disturbance rejection efficacy than the other proposed methods.